AN ANALYSIS OF CONNOTATION AND DENOTATION IN UNPAM VIKTOR’S SIGNS USING BARTHES MODEL - Nur Aliyah; Ana Setyaningsih; Maqhfira Inzani; Muftia Nurcahyani (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
Abstract This study examines the connotation and denotation of signs at UNPAM Viktor using Barthes' semiotic model to explore their explicit and implicit meanings. Employing a qualitative descriptive design, the research analyzes 20 selected signs, highlighting their functional and symbolic roles within the campus environment. The findings reveal that these signs reflect the cultural, social, and institutional values of the university, serving as effective tools for communication and identity reinforcement. This study underscores the importance of Barthes' semiotic theory in interpreting signs in academic contexts and suggests further exploration of how cultural nuances and technological advancements influence sign interpretation. Keywords: Connotation, Denotation, Barthes, Signs, Academic Environment, UNPAM Viktor, Semiotic Analysis